The Intricate Relationship between Strategic Risk Management (SRM) And Strategic Agility In Semiconductor Industry - Lai, Sing Er; Helen Tan, Siew Hong (2023)
Manufacturing semiconductors is pivotal to Malaysia's economic growth and technological advancement. In terms of semiconductor exports, Malaysia ranks seventh worldwide. Malaysia's competitiveness has been enhanced by foreign investment and job creation. However, amidst the changing business landscape, strategic agility has emerged as a crucial organizational skill, allowing firms to swiftly adapt to market shifts, technological advancements, and customer demands. This paper aims to bridge the existing gap in the literature by examining the complex relationship between strategic risk management (SRM) and firm strategic agility within the semiconductor manufacturing sector. In spite of previous research exploring these concepts separately, limited empirical evidence connects strategic risk mitigation strategies to a firm's strategic agility, especially in change management settings. The research seeks to address this gap by addressing three key research questions: 1) The relationship between strategic risk identification and a firm’s strategic agility; 2) The impact of strategic risk assessment methods on a firm’s strategic agility; and 3) The association between strategic risk mitigation strategies and a firm’s strategic agility. This study contributes to a comprehensive understanding of the interplay between SRM and strategic agility, offering insights crucial for organizations to navigate dynamic business environments effectively.